Resort spraw wewnętrznych wobec wyborów czerwcowych w 1989 roku. Decyzja nr 012/89 Ministra Spraw Wewnętrznych z dnia 31 V 1989 w sprawie wprowadzenia stanu podwyższonej gotowości do działań w resorcie spraw wewnętrznych na okres wyborów - Galij-Skarbińska, Sylwia (Fides, Ratio et Patria. Studia Toruńskie, 2018)
During the elections in June 1989, a special staff was established in the Ministry, which was responsible for the operational security of their course. At the same time, an intensive and extensive action was carried out against the opposition candidates and the entire opposition environment. The first structural changes took place only in August 1989. However, no new regulations, new directional plans for operational work, the liquidation of old units and the appointment of new ways, the style and purpose of the SB did not change. He was focusing around the “solidarity” camp and the opposition organizations being formed.